Makerspaces in Libraries: Technology as Catalyst for Better Learning, Better Teaching - Tod Colegrove, Patrick (Ingeniería Solidaria, 2017)
Introduction: Across disciplines, the practice of education continues to evolve. Supporting organizations such as the library are responding by reworking existing practices while developing new ones. With roots grounded deeply in constructivist learning theory, the emerging practice of makerspaces in libraries is proving an effective step in that evolution. The article was written in the year 2016 at the University of Nevada, Reno.Methodology: Examples of associated active learning activity at one such library —an early adopter and first mover among academic libraries in adopting and integrating makerspace in libraries— are presented.Results and Conclusions: The product of leveraging technology as catalyst for active learning and engagement within and beyond the physical commons of the library, a blending of formal and informal learning, leading to increased innovation, entrepreneurship and collaboration across disciplinary and organizational boundaries, appears a natural result.
Keywords: active learning; emerging technology; future of libraries; innovation; makerspace